Effect of mashing-in temperature on free amino nitrogen concentration and foam stability of beer - Cvengroschová, Mariana; Šepeľová, Gabriela; Šmogrovičová, Daniela (BrewingScience, 2003)
Low mashing-in temperature (37°C) and long duration of resting (60 min. including mashing-in) and long time of heating up to 63°C leads to very high amount of FAN – up to 270 mg/l in 12° P wort, but to very poor foam stability of beer produced (220 seconds in average) due to a low amount of high molecular proteins. When mashing-in temperature was higher (63°C) the FAN concentrations of 12°P wort was only 162 mg/l, but foam stability of beer was higher – 268 seconds in average. Mashing-in temperature of 50°C leads to respectable FAN concentration. Yeasts utilised 104 mg/l of FAN in average using 13.5°P wort with initial FAN concentration of 235 mg/l, 90 mg/l using 12.5°P wort (initial FAN – 219 mg/l) and 87 mg/l using 10.5°P wort (initial FAN – 197 mg/l). During maturation process any decrease of FAN was registered. FAN content was dropped due to blending of beer with deoxygenated water by automatic HGB system for desiderative resultant gravity. FAN content in finished product varied from 85 to 106 mg/l for 12°P beer, and from 70 to 94 mg/l for 10°P.